Pengaruh pendidikan kesehatan melalui video terhadap pengetahuan dan praktik mobilisasi dini pada pasien post sectio caesarea - Yulia Sari; Heru Subaris Kasjono; Yuliantisari Yuliantisari (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: The number of sectio caesarean (SC) births in Indonesia is always increasing, with an incidence of around 30-80% of total births. Knowledge about early mobilization is the driving force for post-SC mothers to perform early mobilization well.Objectives: The research aims to determine the effect of health education via video on the knowledge and practice of early mobilization in post-SC patients at RSUD Drs. H. Abu Hanifah.Methods: The research is experimental research conducted at RSUD Drs. H. Abu Hanifah in March - April 2023. The experimental design used was static group comparison, where the experimental group was given health education using video media and the control group using leaflet media. The population is mothers giving birth by caesarean section. Samples were taken by accidental sampling, 22 each for the experimental group and control group. Data collection was carried out using a questionnaire for level of knowledge and a checklist for early mobilization practices. The data analysis technique used the independent sample t test.Results: The results of the study showed that health education through video media had an effect on increasing knowledge (p=0,000) and on early mobilization practices (p=0,005) in mothers giving birth by caesarean section at Drs Regional Hospital. H. Abu Hanifah.Conclusion: Health education via video has an influence on the knowledge and practice of early mobilization in post-SC patients at RSUD Drs. H. Abu Hanifah.KeywordsKnowledge, Early Mobilization Practices, Sectio Caesarea, Video, Leaflet